Accounting Information Usefulness in Credit Risk Evaluation by Banks (gjstudies, 2014)
This research investigates the evolving utility of traditional accounting information in the context of bank credit risk evaluation, proposing a novel, hybrid analyticalframework that integrates conventional financial statement analysis with emerging,non-parametric pattern recognition techniques inspired by ecological succession models. While accounting data has long been the cornerstone of credit assessment, itsstandalone predictive power in contemporary, volatile economic environments is increasingly questioned. This study posits that the diminishing marginal informativeness of historical cost-based accounting figures can be counteracted by a synergisticmethodology that re-contextualizes them within a dynamic, systems-based model offirm resilience and adaptive capacity. Our primary research questions explore: (1) Towhat extent can a bio-inspired, successional analysis of financial statement sequencesenhance the predictive accuracy of default risk beyond standard ratio analysis? (2)How does the integration of qualitative, narrative disclosures—processed through anovel semantic trajectory mapping—alter the weight assigned to quantitative accounting metrics in a holistic risk score? We develop and test the Ecological Succession CreditEvaluation Model (ESCEM), which treats a firm’s multi-period financial statements asan ecological community, identifying successional stages (pioneer, establishment, climax, disturbance) and calculating resilience indices based on the volatility and recoverypatterns of key accounting variables. Concurrently, we apply trajectory divergence algorithms to management commentary to assess strategic consistency. Testing on alongitudinal dataset of corporate borrowers from 1995-2004, our results demonstratethat the ESCEM framework improves default prediction accuracy by approximately18% compared to a benchmark Z-score model, with the most significant gains observedfor firms in transitional or distressed successional stages. The findings challenge theprevailing dichotomous view of accounting information as either useful or obsolete, arguing instead for its reconceptualization as a core input into a more complex, adaptivesystem of firm health. This represents a fundamental shift from static, point-in-timeassessment to a dynamic, process-oriented evaluation of creditworthiness, offering anovel pathway for enhancing the robustness of bank lending decisions in the face ofeconomic uncertainty